3-Nitropropionic Acid-Induced Ischemia Tolerance in the Rat Brain is Mediated by Reduced Metabolic Activity and Cerebral Blood Flow. Issue 9 (September 2014) - Bracko, Oliver; Pietro, Valentina Di; Lazzarino, Giacomo; Amorini, Angela M; Tavazzi, Barbara; Artmann, Judith; Wong, Eric C; Buxton, Richard B; Weller, Michael; Luft, Andreas R; Wegener, Susanne
Tissue tolerance to ischemia can be achieved by noxious stimuli that are below a threshold to cause irreversible damage ('preconditioning'). Understanding the mechanisms underlying preconditioning may lead to the identification of novel therapeutic targets for diseases such as stroke. We here used the oxidative chain inhibitor 3-nitropropionic acid (NPA) to induce ischemia tolerance in a rat middle cerebral artery occlusion (MCAO) stroke model. Cerebral blood flow (CBF) and structural integrity were characterized by longitudinal magnetic resonance imaging (MRI) in combination with behavioral, histologic, and biochemical assessment of NPA-preconditioned animals and controls. Using this approach we show that the ischemia-tolerant state is characterized by a lower energy charge potential and lower CBF, indicating a reduced baseline metabolic demand, and therefore a cellular mechanism of neural protection. Blood vessel density and structural integrity were not altered by NPA treatment. When subjected to MCAO, preconditioned animals had a characteristic MRI signature consisting of enhanced CBF maintenance within the ischemic territory and intraischemic reversal of the initial cytotoxic edema, resulting in reduced infarct volumes. Thus, our data show that tissue protection through preconditioning occurs early during ischemia and indicate that a reduced cellular metabolism is associated with tissue tolerance to ischemia.